Analysis of Extracellular RNA by Digital PCR - Takahashi, Kenji; Yan, Irene K.; Kim, Chaeyoung; Kim, Jungsu; Patel, Tushar (Frontiers in Oncology, 2014)
The transfer of extracellular RNA is emerging as an important mechanism for inter-cellular communication. The ability for the transfer of functionally active RNA molecules from one cell to another within vesicles such as exosomes enables a cell to modulate cellular signaling and biological processes within recipient cells. The study of extracellular RNA requires sensitive methods for the detection of these molecules. In this methods article, we will describe protocols for the detection of such extracellular RNA using sensitive detection technologies such as digital PCR. These protocols should be valuable to researchers interested in the role and contribution of extracellular RNA to tumor cell biology.